PENGARUH UKURAN DEWAN KOMISARIS, KEAHLIAN DEWAN KOMISARIS, DAN PENDIDIKAN PRESIDEN KOMISARIS TERHADAP KINERJA KEBERLANJUTAN PERUSAHAAN YANG LISTED DI BEI - Shanaya Adinda Saputri (2022)
This is quantitative research that aims to analyze the influence of board of commissioners' size, board of commissioners' expertise, and president of commissioners' education on companies' sustainability performance through economic, environmental, and social aspects. The data used are secondary data obtained from annual reports and sustainability reports of non-financial sector companies listed on Indonesia Stock Exchange in 2018-2020. Total sample of this research was 135 and the data were tested using the STATA program. The results reveal that (1) board of commissioners' size has a significant and positive effect on economic sustainability performance, (2) board of commissioners' size has no significant effect on environmental sustainability performance, (3) board of commissioners' size has no significant effect on social sustainability performance, (4) board of commissioners' expertise has no significant effect on economic sustainability performance, (5) board of commissioners' expertise has no significant effect on environmental sustainability performance, (6) board of commissioners' expertise has no significant effect on social sustainability performance, (7) president of commissioners' education has no significant effect on economic sustainability performance, (8) president of commissioners' education has no significant effect on environmental sustainability performance, (9) president of commissioners' education has no significant effect on social sustainability performance.